Radiocarbon age offsets between two surface dwelling planktonic foraminifera species during abrupt climate events in the SW Iberian Margin - Ausín, Blanca (2020)
This study identifies temporal biases in the radiocarbon ages of the planktonic foraminifera species Globigerina bulloides and Globigerinoides ruber (white) in a sediment core from the SW Iberian margin (so‐called Shackleton site). Leaching of the outer shell and measurement of the radiocarbon content of both the leachate and leached sample enabled us to identify surface contamination of the tests and its impact on their 14C ages. Incorporation of younger radiocarbon on the outer shell affected both species and had a larger impact downcore. Interspecies comparison of the 14C ages of the leached samples reveal systematic offsets with 14C ages for G. ruber being younger than G. bulloides ages during the last deglaciation and part of the Early and mid‐Holocene. The greatest offsets (up to 1,030 years) were found during Heinrich Stadial 1, the Younger Dryas, and part of the Holocene. The potential factors differentially affecting these two planktonic species were assessed by complementary 14C, oxygen and carbon isotopes, and species abundance determinations. The coupled effect of bioturbation with changes in the abundance of G. ruber is invoked to account for the large age offsets. Our results highlight that 14C ages of planktonic foraminifera might be largely compromised even in settings characterized by high sediment accumulation rates. Thus, a careful assessment of potential temporal biases must be performed prior to using 14C ages for paleoclimate investigations or radiocarbon calibrations (e.g., marine calibration curve Marine13, Reimer et al., 2013, https://doi.org/10.2458/azu_js_rc.55.16947).